2013
DOI: 10.1371/journal.pone.0066546
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Role of Indoleamine 2,3 Dioxygenase in Mouse Models of Influenza A Virus Infection

Abstract: Influenza infection stimulates protective host immune responses but paradoxically enhances lung indoleamine 2,3 dioxygenase (IDO) activity, an enzyme that suppresses helper/effector T cells and activates Foxp3-lineage regulatory CD4 T cells (Tregs). Influenza A/PR/8/34 (PR8) infection stimulated rapid elevation of IDO activity in lungs and lung-draining mediastinal lymph nodes (msLNs). Mice lacking intact IDO1 genes (IDO1-KO mice) exhibited significantly lower morbidity after sub-lethal PR8 infection, and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 42 publications
6
54
0
Order By: Relevance
“…An initial study in 1979 by Yoshida et al [527] reported the robust induction of IDO1 and the Kyn pathway in the lungs of influenza virus-infected mice, a finding subsequently replicated by others [475, [528][529][530]. Recent data indicate that lung influenza infection elicits IFN-independent IDO1 expression in haematopoietic cells of the draining lymph node, whereas IDO1 expression in the non-haematopoietic epithelial cells of the lung is IFNγ -dependent [530].…”
Section: Expression Of Ido1 In Vitro and In Vivo In Response To Viralmentioning
confidence: 93%
See 2 more Smart Citations
“…An initial study in 1979 by Yoshida et al [527] reported the robust induction of IDO1 and the Kyn pathway in the lungs of influenza virus-infected mice, a finding subsequently replicated by others [475, [528][529][530]. Recent data indicate that lung influenza infection elicits IFN-independent IDO1 expression in haematopoietic cells of the draining lymph node, whereas IDO1 expression in the non-haematopoietic epithelial cells of the lung is IFNγ -dependent [530].…”
Section: Expression Of Ido1 In Vitro and In Vivo In Response To Viralmentioning
confidence: 93%
“…Although influenza virus was reported to induce the robust expression of IDO1 within the lung of infected animals back in 1979 [527], insights into the potential role of the enzyme in influenza infection have only recently been forthcoming. In murine influenza, inhibition of IDO1 activity in wild-type mice with 1-DL-MT or infection of IDO1 −/− mice, enhanced the primary immune response to infection by increasing the production of macrophage-derived pro-inflammatory cytokines, promoting CD4 + and CD8 + T-cell function, as well as Th1 responses [529,530]. Secondary immune responses are also affected, as 1-DL-MT treatment or Ido1 gene deficiency also resulted in elevated effector CD4 + Th1 and Th17 responses, increased the number of effector memory CD8 + T-cells, altered the memory CD8 + T-cell repertoire and decreased numbers of CTLA-4-expressing Tregs [529,530,553].…”
Section: Role Of Ido1 In Virus Infection In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, Trp depletion inhibits T cell immunity and, moreover, the oxidation of Trp by IDO1 generates Kyn derivatives, which promote T cell tolerance by induction of regulatory T cells (121) (Figure 4). Therefore, mice lacking IDO1 exhibit significantly lower morbidity after sub-lethal influenza A infection by generating a stronger influenza-specific effector CD8 T cell response, though viral clearance rates are unaffected by IDO1 ablation (127). Similarly, genetic ablation of IDO1 or chemical inhibition with 1-methyl- d - l -tryptophan suppresses viral replication of murine leukemia virus in vivo and upregulates type I IFN production (128).…”
Section: Amino Acid Metabolism and Ifnsmentioning
confidence: 99%
“…Interestingly, 41 of the 199 druggable cellular factors were shown to be implicated in IAV infection (Table S2) [10,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,...…”
Section: Combination Of Various Omics Techniques Identifies Potentmentioning
confidence: 99%